Book Review Education Policy: Globalization, Citizenship and Democracy - Çetin Toraman (Sakarya University, 2014)
In today's world, countries are facing with the fact that they are getting more global day by day. Accordingly, education is getting more complex and there is an increasing cultural and ethnic diversity among schools. This also has an impact on educational policies. Mark Olssen, John Codd and Anne-Marie O'Neill describe how educational policies should be made and applied in their 12-chapter-book "Education Policy: Globalization, Citizenship and Democracy" which also focuses on cultural, social and political foundations of educational policies.In Chapter 1, the authors mainly discuss latest debates and issues concerning globalization. They also emphasize the importance setting main concepts about globalization. In addition to this, the authors make a clear view between educational policies of nation-states and recent global context which has an extremely importance in understanding the basics of globalization.Chapter 2 whose name is "The Post-structuralism of Foucault." mainly discusses the ideas of Michel Foucault on his concepts of power, knowledge, discourse and government. The authors also mention how Foucault differs from other post-structuralists by explaining his concept of "neoliberalism". To make a theoretical framework, the authors draw attention to Foucault's theories and concepts in relation to social sciences.In Chapter 3 and 4, the authors mainly point out the Foucauldian approach with its own style of criticm which makes it unique. They also discuss on critical policy analysis with the help of his methods of archaeology and genealogy. In chapter 4, the writers expand the framework by pointing out the issues concentrating on an analysis of policy as discourse and as text based upon a materialist theory of language.Chapter 5 makes a clear outline on political rationality of classical liberalism. At that point, the writers highlight the historical developments beginning from seventeenth century with John Locke. And then they draw attention to Adam Smith in eighteenth century and eventually they make an emphasis on Jeremy Bentham in nineteenth century. In the following part, Chapter 6, the writers mainly focus on rise of social democratic or welfare state liberalism. They mention both its emergence and its reflections on economic formulations in nineteenth century. In Chapter 7, domination of neoliberalism is mentioned. Increasing influence on state policy is in the centre of twentieth century. In addition to this, the writers examplify the topic with the academic discourse of economics in writers such as Frederick A. Hayek, James Buchanan etc. and theories such as Public Choice Theory, Human Capital Theory. To make a connection with the education, the writers mention that these are important in understanding of the resurgence of neoliberal restructuring of education and society that has occurred in the western world over the past 20 years. In the next part, in Chapter 8, neoliberalism's effect on educational management. It also emphasizes the impact of neoliberalism in reconstructing institutions. To make a summary for Chapter 5, 6, 7 and 8, it can be said that they all try to concentrate on themes of liberalism and the effects of liberal reason on models and conceptions of education.In Chapter 9, it is mentioned that neoliberalism affect the structure of higher education. The writers point out that neoliberalism affect the professionalism as well as competition on culture of trust. Accordingly, they examine educational restructing in England and New Zealand by comparing similarities and contrasts.Chapter 10 mainly discusses the neoliberal policies of choice including school choice, inequality and discourses of diversity. In Chapter 11, by comparing liberal to communitarian forms of governmentality, the writers examine different educational policy topics in their contexts. The writers also point out their endorsement of a communitarian position by stating that a more viable political theory is needed to understand the role of the government in citizenship and democracy education in a global context. Finally, in Chapter 12, the writers make a conclusion by summarizing the issues held in the previous chapters. In this chapter, they focus globalization's importance on citizenship and democracy education. Moreover, a new conception of political formulation based on democracy and education is discussed to summarize the issue.According the reviewer, this book is highly beneficial for researchers in the field of education, especially for those who mostly study on democracy and human rights issues. Furthermore, sociologists can benefit from this book while analyzing sociological foundations of human rights, citizenship and democracy.Olssen, M., Codd, J.,O'Neill, A. (2004) Education Policy: Globalization, Citizenship and Democracy. London: SAGE Publications. ISBN 0 7619 7469 5